Pengaruh Pergantian Auditor, Reputasi KAP, Opini Audit, Komite Audit dan Ukuran Perusahaan terhadap Audit Delay - Putri Rahmadhanni; Agustiawan Agustiawan; Muhammad Ahyaruddin (Universitas 45 Surabaya, 2024)
This study aims to examine the effect of auditor turnover, KAP reputation, audit opinion, audit committee and company size on audit delay. The research method used is quantitative. The total population in this study is 226 industrial sector manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling method uses purposive sampling techniques, so that the number of samples is obtained as many as 91 companies. The data analysis technique uses multiple linear regression analysis equations with the SPSS program. The results of this study show that changing auditors has a positive ang insignificant effect on auit delay, KAP reputation and audit committee have a significant negative effect on audit delay, audit opinion has an insignificant negative effect on audit delay, while company size has a significant positive effect on audit delay.